Disentangling the relationship of subjective cognitive decline and depressive symptoms in the development of cognitive decline and dementia: alternate format research article - Kleineidam, Luca; Wagner, Michael; Guski, Jannis; Wolfsgruber, Steffen; Miebach, Lisa; Bickel, Horst; König, Hans-Helmut; Weyerer, Siegfried; Lühmann, Dagmar; Kaduszkiewicz, Hanna; Luppa, Melanie; Röhr, Susanne; et al. (Alzheimer's and dementia, 2023)
Abstract Introduction Subjective cognitive decline (SCD) and depressive symptoms (DS) frequently co-occur prior to dementia. However, the temporal sequence of their emergence and their combined prognostic value for cognitive decline and dementia is unclear. Methods Temporal relationships of SCD, DS and memory decline were examined by latent difference score modeling in a high-aged, population-based cohort (N = 3217) and validated using Cox-regression of dementia-conversion. In 334 cognitively unimpaired SCD-patients from memory-clinics, we examined the association of DS with cognitive decline and with cerebrospinal fluid (CSF) Alzheimer's disease (AD) biomarkers. Results In the population-based cohort, SCD preceded DS. High DS were associated with increased risk of dementia conversion in individuals with SCD. In SCD-patients from memory-clinics, high DS were associated with greater cognitive decline. CSF Aß42 predicted increasing DS. Discussion SCD typically precedes DS in the evolution to dementia. SCD-patients from memory-clinics with DS may constitute a high-risk group for cognitive decline. Highlights Subjective cognitive decline (SCD) precedes depressive symptoms (DS) as memory declines. Emerging or persistent DS after SCD reports predict dementia. In SCD patients, more amyloid pathology relates to increasing DS. SCD patients with DS are at high risk for symptomatic progression.
Erstmals veröffentlicht: 11. Oktober 2022
Gesehen am 01.07.2024